2016
DOI: 10.1007/s11121-016-0665-0
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Parenting as a Multidimensional and Dynamic Construct with a Person-Oriented Approach

Abstract: Although parenting is one of the most commonly studied predictors of child problem behavior, few studies have examined parenting as a multidimensional and dynamic construct. This study investigated different patterns of developmental trajectories of two parenting dimensions (harsh discipline [HD] and parental warmth [PW]) with a person-oriented approach, and examined the associations between different parenting patterns and child externalizing problems and callous-unemotional traits. Data were drawn from the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 50 publications
3
11
0
Order By: Relevance
“…It might also be true that parents of children with low levels of behavior problems who report high parenting self-efficacy, but use lax parenting practices may do so because they recognize that well-behaved children respond best to a parenting approach that involves minimal direction or cajoling (Neger 2015). As a whole, these findings reinforce the recent view that “parenting dimensions are not expressed alone but interact with other dimensions in a complex and transactional system” (Zheng, Pasalich, Oberth, McMahon, & Pinderhughes; 2017, p. 282).…”
Section: Discussionsupporting
confidence: 87%
“…It might also be true that parents of children with low levels of behavior problems who report high parenting self-efficacy, but use lax parenting practices may do so because they recognize that well-behaved children respond best to a parenting approach that involves minimal direction or cajoling (Neger 2015). As a whole, these findings reinforce the recent view that “parenting dimensions are not expressed alone but interact with other dimensions in a complex and transactional system” (Zheng, Pasalich, Oberth, McMahon, & Pinderhughes; 2017, p. 282).…”
Section: Discussionsupporting
confidence: 87%
“…The results of this study indicate that including multiple direct observational measures of parenting is labor well spent, in that our findings confirm a multifaceted model of parenting (Zheng et al., ). First, separate measures of parental behavior (i.e., positive/negative and cognitive/affective) show distinct patterns of association with children's EF.…”
Section: Discussionsupporting
confidence: 84%
“…Supporting a differentiated view of parental behavior (e.g., Carr & Pike, ; Hughes & Ensor, ; Zheng, Pasalich, Oberth, McMahon, & Pinderhughes, ), our results showed that parental behaviors can be measured along distinct cognitive and affective dimensions. For instance, the correlation matrix shows that negative parent–child interaction was inversely related to parental talk (MLU).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The third paper by Zheng, Pasalich, Oberth, McMahon, and Pinderhughes (in press) describes a person-oriented approach to measuring parenting, intended to capture the multidimensional and dynamic nature of parenting. The authors describe the use of growth mixture modeling to characterize patterns of harsh discipline and parental warmth over time.…”
Section: Motivation For This Seriesmentioning
confidence: 99%